2162. Risk Factors Associated with Hospitalization among 0 to 21 Years Old Patients with Active Asthma/Active Airway Disease: Preliminary Findings from Multi-Center Study Across United States. (15th December 2022) - Pardasani, Sapna; Dallas, Ronald H; Ross, Hailey S; Ferrolino, Jose A; Fisher, Brian T; Danziger-Isakov, Lara A; Muller, William J; Maron, Gabriella; Kitt, Eimear
Abstract: Background: More data are needed to understand the risk for COVID-19 severity among pediatric asthma patients. We present findings from a national registry characterizing COVID-19 hospitalizations among pediatric asthma patients. Methods: Data were obtained from the Pediatric COVID-19 US Registry, which included medical records of COVID-19 cases < 21 years old between March 2020 and May 2021. Those with asthma were eligible while immunocompromised and transplant cases were excluded. Descriptive statistics and chi-square tests were performed. Results: Of the 1089 eligible asthma cases, half were 12 to 17 years old [Figure 1], the majority were male [Figure 2], a third Black African American [Figure 3], and most were Non-Hispanic/Latino 825 (76%). 242 (22%) reported a history of smoking. A fourth of cases (257 (23.6%) were hospitalized for COVID-19. More than half (54%) reported asthma as their only pre-existing condition. The majority (n=71, 28%) were taking regular inhaled corticosteroids. Almost half (n=120, 47%) had abnormal chest radiographic findings, 20 (7.8%) had abnormal CT findings, and 24 (9%) progressed to lower respiratory infection. About 10% (n=25) needed mechanical ventilation. A third (n=88, 34%) required ICU care with 33% of those receiving inhaled corticosteroids. A quarter needed mechanical ventilation [Figure 5]. Compared to asthma patients not hospitalized for COVID-19, those hospitalized were significantly (P< 0.05) more likely to be non-Hispanic, have multiple pre-existing conditions, and be obese [Figure 6]. Compared to those not admitted to ICU, ICU cases were significantly more likely to be obese and be diagnosed with MIS-C [Figure 7]. Demographics The majority of cases (N=479, 44%) were between 12 and 17 years old, Male (N=610, 56%) and Black or African American (N=410, 38%). Clinical Characteristics Risk factors assessment Conclusion: This is one of the first national studies examining COVID-19 among pediatric cases with asthma. Our data suggest that children with asthma who have multiple pre-existing conditions and/or are obese have a higher risk for hospitalization. These early data may aid clinicians in developing future prospective studies to understand COVID-19 risk among this vulnerable population. Disclosures: Lara A. Danziger-Isakov, MD, Ansun BioPharma: Contracted clinical research|Astellas: Contracted clinical research|GSK: Advisor/Consultant|Merck: Advisor/Consultant|Merck: Contracted clinical research|Pfizer: Contracted clinical research|Takeda: Grant/Research Support|Takeda: Contracted clinical research|Viracor: Grant/Research Support.